ANALYSIS OF VISUAL REPRESENTATION OF CO-BRANDING THROUGH PACKAGING DESIGN: A CASE STUDY OF DERMIES HELLO GLOW BY ERHA AND TEH BOTOL SOSRO - Zhalika Cantara Adzani; Rully (Journal Informatic, Education and Management (JIEM), 2026)
Co - branding has become a popular strategy to create added value through brand collaborations from different industries . In this kind of collaboration , packaging design plays a crucial role in communicating the identity and values ​​of the partnering brands . This study aims to analyze the visual representation of co-branding in the packaging designs of Dermies Hello Glow by ERHA and Teh Botol Sosro . A descriptive qualitative method was used with visual observation and literature review techniques . The analysis focuses on how visual elements such as color , typography , illustration , logo, and imagery contribute to representing the collaboration between the two brands . The findings show that the packaging successfully integrates the visual identities of Dermies Hello Glow and Teh Botol Sosro through the use of tea- themed colors , tea leaf illustrations , and the iconic silhouette of the Teh Botol Sosro bottle . These elements reinforce the co-branding message while supporting the ingredient branding concept . The study concludes that packaging design serves as an effective visual communication medium to express co-branding values ​​and create a unified brand experience .